Mongolia : Fourth Review under the Stand-By Arrangement and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses key findings of the Fourth Review Under the Stand-By Arrangement for Mongolia. All end-December performance criteria were met, and the indicative limit on the fiscal deficit was met with a comfortable margin. Inflation, after falling rapidly into negative territory for the past few months, has swung upward and could reach 8 percent. The flexible exchange rate regime continues to work well, and the central bank has intervened sparingly in recent months. The key macromanagement priorities in the period ahead will be to contain inflation and maintain fiscal discipline.